Management of and Potential Return on Private Investments in Latvian Sports - Mārtiņš Lauva; Uldis Grāvītis (Lithuanian Sports University, 2018)
Background. Latvian sports authorities under the Ministry of Education and Science are the main organisers of the sports life in Latvia. However, they have not been successful in providing equally good support to all athletes who need it. It is especially difficult to receive support for improving skills of individual athletes engaged in team sports. Often it is the individual mastery of an athlete that prohibits them from moving on to the adult level of sports of high achievement, even if the athlete was very talented and one of the best in the country when he/she was young. Methods.  The  descriptive  statistics  method  and  content  analysis  were  used  to  assess  shortcomings  in  the allocation of finances in the Latvian sports industry. Conclusions were drawn on the data collected, on the basis of which a new method was developed in sports management, the efficiency of which was verified by performing an experiment. Results. After analysing the most popular sports among young people in the country, as well as the available infrastructure, it may be suggested which sports are the most attractive for investors. It may be concluded that the state is able to successfully solve this problem by attracting private investors who would be personally interested in the development of athletes and also carry out successful investment management. The study demonstrated that a successful process of private investments ensures a positive return on the investments, as well as the development of athletes. One way to build successful cooperation is by creating high-quality sports development centres or sports investment management companies which will efficiently contribute to athletes' transition from youth to professional sports. The efficiency of the methodology developed can be demonstrated by creating a company which would act as an example for attracting private investments in the development of athletes. Conclusion. The development of athletes would become more efficient and purposeful if sports could attract potential investments with promising returns. This would create a tripartite cooperation among the state, athletes and private investors, which would benefit each of the three cooperating parties. Additional funding in the development of Latvian athletes would have a positive impact on the entire sports industry as a whole. Keywords:  Latvian sports, private investments, sports funding, massive sports system, investment criteria,  high-class sports, sports development, efficient investment management